2006
DOI: 10.1080/15391523.2006.10782461
|View full text |Cite
|
Sign up to set email alerts
|

Learning Strategies and Performance In a Technology Integrated Classroom

Abstract: This study examines students ' use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 13 publications
2
27
0
1
Order By: Relevance
“…Another reason for having such project in Malaysia because students are growing up in the world of technology, using the Internet to search for information is not strange to them anymore. Students like to see lecturers to develop the teaching materials in presentation software such as Microsoft PowerPoint where the multimedia elements (graphics, animation, sound, video and text) can be used to attract the students' attention [2]. The use of technology in the classroom has not increased much on the learner-centred practices.…”
Section: B Technology In Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason for having such project in Malaysia because students are growing up in the world of technology, using the Internet to search for information is not strange to them anymore. Students like to see lecturers to develop the teaching materials in presentation software such as Microsoft PowerPoint where the multimedia elements (graphics, animation, sound, video and text) can be used to attract the students' attention [2]. The use of technology in the classroom has not increased much on the learner-centred practices.…”
Section: B Technology In Educationmentioning
confidence: 99%
“…With these new applications and learning platform, students are exposed to a more student-centred learning experience. Reference [2] posited "the use of computer-based technology in college education has dramatically increased to include emerging technology for visual presentation, simulation, accessing course materials and World Wide Web resources, and interactivity".…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified benefits such as keeping students on task and engaged (Hyden, 2005), or following lectures via PowerPoint or multimedia (Debevec, Shih & Kashyap, 2006). However, other research indicates that using laptops in class can be a disadvantage (Fried, 2008).…”
Section: Overviewmentioning
confidence: 99%
“…Three main types of assignments are distinguished: 1) searching and playing 2) cognitive-searching and 3) cognitive-researching [8].…”
Section: The Consequence Of Pedagogical Conditions For Forming Foreigmentioning
confidence: 99%